Método de extração de linha de produtos de software baseado em testes - Alcemir Rodrigues Santos (2013)
Many software systems have been developed as single products before Software Product Lines (SPLs) have emerged. Although some promising approaches have been proposed, extracting an SPL from existing software products is still expensive and time consuming. This work presents a method to extract an SPL from single products that relies on software testing already developed. We evaluate testing as the main mean to locate feature code and different sorts of existing artifacts to support the test-based location. We conduct three case studies starting from the derivation of the SPL feature model to the feature code location. Our results indicate (i) interesting rates of precision for feature seed location, where seed means a small portion of the feature code that allows the identification of the remaining portion, and (ii) good rates of recall for locating the whole feature code.